PENGARUH KINERJA KEUANGAN PADA PENGUNGKAPANCORPORATE SOCIAL RESPONSIBILITY PERUSAHAAN MANUFAKTUR DI BEI - Afrianto, Kus; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to test how the influence of financial performance to the Corporate Social Responsibility (CSR). The independent variables in this research are firm size, profitability, leverage and the size of board of commissioner. The dependent variable in this research is the corporate social responsibility disclosure which is measured by using the 78 indicators of CSR disclosure. The samples are all manufacturing companies which are listed in Indonesian Stock Exchange (BEI) in 2012-2014 periods. The samples have been selected by using purposive sampling method and 26 companies have been selected as samples. The data is secondary data which is in the form of the annual report of manufacturing company. The analysis method has been done by using multiple regression analysis.The result of the research shows that CSR disclosure and practice as the field of accounting significantly has been influenced by the firm size and the size of board of commissioner. Other factors which have been examined in this research such as profitability and leverage does not have any influence the CSR disclosure which has been carried out by the company.Keywords: Corporate social responsibility, firm size, profitability, leverage and the size of the board of commissioner.